Strategies and Challenges in Global Talent Management: Developing an Integrated Approach for Multinational Corporations - Heinonen, Lauriina (My University, 2024)
Global Talent Management (GTM) is an emerging and highly regarded field, which focuses on the efficient management of the human capital of the organization to promote competitive advantage. This thesis offers a comprehensive examination of global talent management, aiming to bridge the conceptual gaps within the field and propose an integrated GTM framework approach suitable for multinational corporations (MNCs) in GTM implementation. The thesis highlights the strategic importance and nature of GTM. Through a systematic literature review the thesis collects some of the various challenges MNCs face with GTM and elements and processes the comprise GTM systems. As a result of the extensive discussion of the GTM system and factors of human resource management the thesis presents an integrated framework approach to GTM. The thesis presents theoretical contributions by bridging gaps in literature of offering comprehensive discussions from definitions to the GTM system and providing an integrated approach to promote future research avenues. This work contributes to the theoretical and practical discourse on GTM, proposing a multifaceted perspective that considers organizational, cultural, and ethical dimensions for advancing talent management globally. Practical relevance is drawn from the use and benefits of clarifying GTM definition and boundaries in addition to the integrated framework approach that involves various stakeholders in multiple ways. Ultimately the thesis provides discourse in GTM concepts without neglecting its limitations to offer excitement and opportunities for further research.

Kansainvälisten kyvykkyyksien johtaminen on nouseva ja arvostettu ala, joka keskittyy henkisen pääoman tulokselliseen johtamiseen kilpailuedun kehittämiseksi. Tämä pro gradu -tutkielma tarkastelee kattavasti kansainvälisten kyvykkyyksien johtamista ja pyrkii selventämään alan käsitteellisiä puutteita sekä esittämään monikansallisille yrityksille soveltuvan yhtenäisen viitekehyksen kansainvälisten kyvykkyyksien johtamiselle. Kattavassa kirjallisuuskatsauksessa esitetään yleisimpiä haasteita, joita kansainväliset yritykset kohtaavat kansainvälisten kyvykkyyksien johtamisessa, sekä elementtejä ja prosesseja, joista näiden järjestelmät koostuvat. Tarkastelemalla kattavasti kansainvälisten kyvykkyyksien ja henkilöstöhallinnon tekijöitä tutkielma tarjoaa integroidun viitekehyksen kansainvälisten kykyjen johtamiselle. Teoreettisella tasolla tutkielma pyrkii täydentämään kirjallisuudessa esiintyviä aukkoja kansainvälisten kyvykkyyksien johtamisen määritelmille ja tarjoaa integroidun lähestymistavan jatkotutkimuksille. Tämä tutkielma tarjoaa kansainvälisten kyvykkyyksien johtamisen ajatuksenvaihdolle monipuolisen perspektiivin, joka huomioi eri osa-alueita, kuten esimerkiksi organisatorisia haasteita, kulttuurillisia seikkoja ja eettisiä näkökulmia. Käytännön merkitystä voidaan ammentaa eri sidosryhmien rooleista ja hyödyistä, jotka on sisällytetty järjestelmän eri osa-alueisiin ja huomioitu kunkin osa-alueen toteutuksessa. Lopuksi tutkielma tarjoaa, rajoitteensa huomioiden, herätteitä kansainvälisten kyvykkyyksien johtamiseen tavoitteenaan innostaa ja mahdollistaa aiheen jatkotutkimuksia.
Keywords: Global Talent Management, International Human Resource Management, Talent Management, Multinational Corporations